Worm control approaches and their impact on status of anthelmintic resistance at an organized sheep farm - SINGH, D; SWARNKAR, C P (The Indian Journal of Animal Sciences, 2017)
The aim of study was to ascertain efficiency of different worm management strategies in reversion to susceptibility to anthelmintics in sheep maintained at Sheep Breeding Farm, Fatehpur (Rajasthan). An increase in efficacy of benzimidazole (BZ) from nil to 14 and 75% was observed after 6 and 8 years of withdrawal, respectively. The restricted use of imidothiazoles enhanced efficacy from 25% in 1998 to 92% in 2007. From 2010, community dilution strategies through introduction of newly purchased sheep were implemented and evaluated for their impact on reversion to susceptibility after 5 years. A marginal increase in BZ efficacy (up to 43%) was observed after introduction of new animals possessing anthelmintic resistant/susceptible worms and rotational use of anthelmintic types. A moderate rise in BZ efficacy (up to 56%) was observed on community dilution through introduction of Nali sheep possessing susceptible Haemonchus contortus and use of BZs and closantel in rotation. A significant increase in BZ efficacy (up to 88%) was noticed on community dilution through introduction of Marwari sheep possessing susceptible H. contortus and application of targeted selective treatment (TST) using closantel. The efficacy of tetramisole (TEM) increased from 25% (1998) to 92% (2007) after 8 years of withdrawal TEM which further increases to 99% (2015) after introduction of TEM susceptible H. contortus through newer sheep coupled with rotation of anthelmintic classes. The results indicated that just withdrawal of ineffective anthelmintic is not sufficient enough to cause evident reversion to susceptibility. However, community dilution coupled with TST with newer class of anthelmintic will help in reversion to susceptibility in gastrointestinal nematodes at faster rate in sheep.